Keterampilan Eksplorasi Sumber Referensi Artikel Ilmiah pada Mahasiswa Calon Guru Sains melalui Pembelajaran Metodologi Penelitian Pendidikan IPA - Parmin; Erna Noor Savitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Prospective science teachers' research proposals are still weak in reference sources because citations from national or international journals are still lacking. The main weakness comes from the reference sources and citation methods. This study aims to measure prospective science teachers' skills in exploring reference sources for scientific articles. Exploratory skills in this research are limited to organizing a theoretical review for a thesis proposal. This research uses mixed methods. Quantitative data is obtained from the score of research proposals prepared by 34 prospective science teachers as research targets, while qualitative data is from analyzing reference sources in research proposals. Each prepares one proposal so that there are 34 research proposals studied. From the results of the proposal assessment, prospective science teachers are still weak in using references that meet the criteria of >80% of journals and reference publication years that meet the criteria of >80% of publications in the last ten years. The study concludes that learning that equips prospective teachers in preparing research proposals requires a curriculum review. Students need more profound knowledge about references, starting from getting to know journals, selecting articles, looking for articles' findings, citing, and compiling a bibliography.